2019
DOI: 10.1021/acs.est.9b03348
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Dissolved Organic Matter Composition and Biolability across Gradients of Glacial Coverage and Distance from Glacial Terminus on the Tibetan Plateau

Abstract: Globally, alpine glaciers hold a large quantity of dissolved organic matter (DOM) and are headwaters of numerous rivers supporting downstream heterotrophic metabolism. However, it remains unclear how glacial coverage and distance from the glacial terminus affect the fate of DOM. Here, we elucidate DOM variability in glacial-fed streams on the Tibetan Plateau using field sampling and bioincubation experiments and compare our findings with the existing literature. We found that dissolved organic carbon, DOM abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 77 publications
4
32
0
Order By: Relevance
“…Concurrently, stream DOM composition became increasingly dominated by terrestrial plant and soil signatures (Table 1, Figures 3 & 4). The observed trends in the streamwater DOM composition with glacier retreat were consistent with previous studies that assessed watersheds with gradients in glacier cover, where low glacier cover was associated with more enriched bulk Despite the ancient aliphatic signature of DOM being a ubiquitous feature of glaciers and their environments, the sources of OM that explain glacier outflow DOM composition remain uncertain (Behnke et al 2020;Bhatia et al 2013;Kellerman et al In Press;Lawson et al 2014b;Singer et al 2012;Spencer et al 2014a;Stubbins et al 2012;Zhou et al 2019a (Behnke et al 2020;Koch and Dittmar 2006). Thus, significant contributions of OM from overridden, subglacial palaeoorganic material are unlikely.…”
Section: Glacier Retreat Driven Changes In Dissolved Organic Matter Compositionsupporting
confidence: 88%
See 1 more Smart Citation
“…Concurrently, stream DOM composition became increasingly dominated by terrestrial plant and soil signatures (Table 1, Figures 3 & 4). The observed trends in the streamwater DOM composition with glacier retreat were consistent with previous studies that assessed watersheds with gradients in glacier cover, where low glacier cover was associated with more enriched bulk Despite the ancient aliphatic signature of DOM being a ubiquitous feature of glaciers and their environments, the sources of OM that explain glacier outflow DOM composition remain uncertain (Behnke et al 2020;Bhatia et al 2013;Kellerman et al In Press;Lawson et al 2014b;Singer et al 2012;Spencer et al 2014a;Stubbins et al 2012;Zhou et al 2019a (Behnke et al 2020;Koch and Dittmar 2006). Thus, significant contributions of OM from overridden, subglacial palaeoorganic material are unlikely.…”
Section: Glacier Retreat Driven Changes In Dissolved Organic Matter Compositionsupporting
confidence: 88%
“…14 C-DOC values(Fellman et al 2014; Hood et al 2009;Zhou et al 2019a) and DOM that contained a large proportion of organic matter (OM) from fresh plant biomass and soil organic material (i.e.,  13 C-DOC depletion and increased % RA of aromatics and HUPs).…”
mentioning
confidence: 99%
“…Rapid microbial use of bio-labile organic carbon in the river may have occurred and may have driven the higher aromaticity of dissolved organic matter in the Yangtze River in comparison to other large rivers of the world; this being supported by the laboratory bio-incubation experiment. A fraction of the carbon was found to be bio-available with a bioavailable DOC of 12-18% over 28 d of bio-incubation in the Yangtze River, which is comparatively lower than in small coastal temperate streams (Fellman et al 2008) and permafrost-fed (Abbott et al 2014) and glacial-fed stream ecosystems (Spencer et al 2014;Zhou et al 2019). The Yangtze River watershed has experienced rapid urbanization during the past three decades and the river now faces numerous eco-environmental challenges.…”
Section: Discussionmentioning
confidence: 98%
“…Transport of terrestrial DOM is generally dependent on steady flow dynamics in flow path/runoff [7,33], and rainfall is seasonal and highly varied in Duliujian River catchment. It was reported that in glacial-fed rivers, DOC, a 254 and aromaticity were enhanced corresponding to the increasing distance from the glacial terminus, which was controlled largely by glacial or snow meltwater [44]. Two aspects (rainfall and buffer distance from water source) were considered to utilize spatial geographic analysis techniques to probe the effect of land use on organic matter in the catchment.…”
Section: Effect Of Land Use On Dom In the Subcatchmentsmentioning
confidence: 99%